Advancements in breeding for high oil content in maize (Zea mays. L) - Getu , Abukiya; Hirko, Biruk (International Journal of Scientific World, 2024)
Maize is one of the world’s most important food crops, supplying>5% deity energy. Due to its wider adaptability, high yield potential, maize is widely utilized as food and animals world worldwide. It enriched with caloric starch and the high energy in its oil. The kernel oil content in commercial high-oil maize hybrids averages ∼8%, far lower than that in developed high-oil maize lines (as high as 20%). The maize seed/kernel consisted of endosperm (82%) and the germ (embryo and scutellum) (12%). The germ region makes up 80–84% of kernel oil, with the aleurone and endosperm making up 12% and 5%, respectively. High-oil maize may serve as a valuable forage maize germplasm for breeding. Maize oil is also considered as high-quality oil for human health due to the high proportion of polyun-saturated fatty acids. Selection for high oil increases the proportion of germ and further content of germ oil. The problems that over-shadow the successful production of high-oil corn are low grain yield potential, physiological cost of oil synthesis, low seed vigor, low kernel weight, shorter seed longevity, and poor germination of high-oil corn lines. It is necessary to make efforts to generate nested populations or use marker-assisted recurrent selection (MARS) to accumulate the advantageous quantitative trait loci (QTLs) in the pa-rental lines. The oil content of maize inbreeds and hybrids could be further improved with the use of transgenes, genomics, and metabolic engineering technologies in new insight for the development of high oil maize breeding and strategies.